Cytogenetic analysis of a multinodular thyroid goiter - Gama, N. B.; Gama, R.; Thome, J. A.; Tajara, E. H. (Elsevier, 1991)
Short-term cultures of a collagenase disaggregated multinodular goiter was shown by cytogenetic analysis to have the mosaic karyotype 47,XX,+7/48,XX,+7,+17/49,XX,+7,+10,+17. No cytogenetic data on goiter are available for comparison with the present case.
Keywords: adult; aneuploidy; autosome mosaicism; case report; chromosome 7; female; goiter; human; human cell; human tissue; priority journal; trisomy; Adult; Case Report; Cells, Cultured; Female; Goiter; Human; Karyotyping; Mosaicism; Support, Non-U.S. Gov't; Thyroid Nodule; Thyroidectomy